In vivo evaluation of photodynamic inactivation using Photodithazine (R) against Candida albicans - Carmello, J. C. [UNESP]; Dovigo, L. N. [UNESP]; Mima, E. G. [UNESP]; Jorge, J. H. [UNESP]; Souza Costa, C. A. de [UNESP]; Bagnato, V. S.; Pavarina, A. C. [UNESP] (Royal Soc Chemistry, 2015)
This study describes the photoinactivation of Candida albicans in a murine model of oral candidosis, mediated by Photodithazine (R) (PDZ). Six-week-old female Swiss mice were immunosuppressed, and inoculated with C. albicans to induce oral candidosis. After five days, photodynamic inactivation (PDI) mediated by PDZ at concentrations of 75, 100, 125 and 150 mg L-1 was applied on the tongue of mice. Next, microbiological evaluation was performed by recovering C. albicans from the tongue via colony forming units (CFU mL(-1)). After 24 h of treatment, the animals were killed and the tongues were surgically removed for histological analysis. PDI was effective in reducing C. albicans on the tongue of mice using 100 mg L-1 of PDZ, when compared to the positive control group (without treatment). No adverse effect on the tongue tissue was verified after PDI. Therefore, PDI was effective for inactivation of C. albicans without causing any harmful effects on host tissues, which is promising for future clinical trials.